The Contribution of Islamic Scholars to the Technological Revolution: Relevance and Inspiration for the Youth of the 21st Century - Jannah, Khofifah Indah Baitul (Islamic Civilization and History, 2024)
The contributions of Islamic scholars during the Islamic Golden Age have played a pivotal role in shaping modern science and technology. Despite their significant influence, there is limited awareness among today's youth regarding the historical relevance of these scholars and their innovations. This study aims to explore the contributions of Islamic scholars to the technological revolution and to highlight their relevance and inspirational value for the youth of the 21st century. A qualitative research approach is utilized, comprising a comprehensive literature review of historical texts, scholarly articles, and educational resources related to key figures such as Al-Khwarizmi, Ibn al-Haytham, and Avicenna. The findings reveal that the principles and methodologies established by these scholars are integral to contemporary scientific practices and can serve as a source of motivation for young people pursuing careers in STEM fields. By integrating these historical contributions into modern educational frameworks, this research advocates for a renewed appreciation of Islamic scholarship and its potential to inspire the next generation of innovators.